Ehrlichia spp. close to Ehrlichia ruminantium, Ehrlichia canis, and “Candidatus Ehrlichia regneryi” linked to heartwater-like disease in Kenyan camels (Camelus dromedarius) - Younan, M.; Ouso, D.O.; Bodha, B.; Keitany, E.K.; Wesonga, H.O.; Sitawa, R.; Kimutai, J.; Kuria, W.; Sake, W.S.; Svitek, Nicholas; Landmann, T.; Wako, Diba Dida; et al. (Springer, 2021)
We present findings from an outbreak of a heartwater-like disease in camels that killed at least 2000 adult animals in Kenya in 2016. Clinical signs included excitability, head pressing, aimless wandering, recumbency, and fast breathing followed by death after about 4 days. The observed morbidity in one herd was 40% with an average mortality of 7.5% in animals that received early antibiotic treatments. In untreated adults, the case fatality rate reached 100%. Gross pathology showed pulmonary edema, pleural exudate, hydrothorax, hydropericardium, ascites, enlarged “cooked” liver, nephrosis, and blood in the abomasum and intestine. Using established PCR-based protocols for tick-borne pathogens, a sequence close to Ehrlichia regneryi and Ehrlichia canis amplified in blood from two sick camels. We also amplified an Ehrlichia sp. sequence close to Ehrlichia ruminantium Welgevonden from a pool of Amblyomma spp. ticks collected from a sick camel and in a pool of Rhipicephalus spp. ticks from healthy camels.